Chronic Rhinosinusitis with Dextra ET Sinistra Nasal Polyps - Lina Marlina; Nildi Selan; Tranggono Yudo Utomo (Indonesian Journal of Global Health Research, 2025)
Chronic rhinosinusitis with nasal polyps is a chronic inflammatory condition of the nasal mucosa and paranasal sinuses, characterized by bilateral polypoid tissue growth. This disease can significantly reduce quality of life due to persistent and recurrent symptoms. This report aims to describe a case of chronic rhinosinusitis with right and left nasal polyps, including risk factors, clinical features, supporting examination results, and patient management and follow-up. This study is a descriptive case report involving one patient with bilateral chronic nasal congestion, anosmia, and rhinorrhea that lasted more than 12 weeks. Data were collected through anamnesis, physical examination, nasoendoscopy, CT scan imaging, and patient medical records. Data analysis was performed qualitatively by describing the clinical course, supporting examination results, therapeutic interventions, and patient follow-up evaluation. The patient experienced significant improvement post-operatively with decreased symptoms, increased quality of life, and no polyp recurrence was found within 3 months after the procedure. Appropriate diagnosis and management of chronic rhinosinusitis with bilateral nasal polyps are essential to prevent complications and improve patient prognosis.